2006
DOI: 10.1038/sj.emboj.7601206
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial control of Arabidopsis proline dehydrogenase transcription by specific heterodimerisation of bZIP transcription factors

Abstract: Proline metabolism has been implicated in plant responses to abiotic stresses. The Arabidopsis thaliana proline dehydrogenase (ProDH) is catalysing the first step in proline degradation. Transcriptional activation of ProDH by hypo-osmolarity is mediated by an ACTCAT cis element, a typical binding site of basic leucine zipper (bZIP) transcription factors. In this study, we demonstrate by gain-of-function and loss-of-function approaches, as well as chromatin immunoprecipitation (ChIP), that ProDH is a direct tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
201
1
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(233 citation statements)
references
References 60 publications
(93 reference statements)
8
201
1
14
Order By: Relevance
“…5). A previous study has shown that group S1 proteins, including AtbZIP1, can form heterodimers with group C bZIP proteins to directly regulate the Arabidopsis Pro dehydrogenase gene (ProDH; At3g30775; Satoh et al, 2004;Weltmeier et al, 2006). Both AtbZIP1 and ProDH were found as RGA up-regulated and KIN10-induced genes in this study, indicating that AtbZIP1 is probably relevant to RGA regulation of floral organ development in response to stress.…”
Section: Expression Analysis Of Immediate Targets Of Rgamentioning
confidence: 59%
See 1 more Smart Citation
“…5). A previous study has shown that group S1 proteins, including AtbZIP1, can form heterodimers with group C bZIP proteins to directly regulate the Arabidopsis Pro dehydrogenase gene (ProDH; At3g30775; Satoh et al, 2004;Weltmeier et al, 2006). Both AtbZIP1 and ProDH were found as RGA up-regulated and KIN10-induced genes in this study, indicating that AtbZIP1 is probably relevant to RGA regulation of floral organ development in response to stress.…”
Section: Expression Analysis Of Immediate Targets Of Rgamentioning
confidence: 59%
“…6, A-C). A previous study has shown that AtbZIP1 forms a heterodimer with group C bZIP proteins to activate the expression of ProDH (At3g30775), which is induced in response to hypoosmotic conditions occurring during rehydration after stress recovery (Satoh et al, 2004;Weltmeier et al, 2006). Interestingly, both AtbZIP1 and ProDH are RGA up-regulated and KIN10-induced genes.…”
Section: Rga Regulates Flower Development By Activating Stress-relatementioning
confidence: 99%
“…The formation of all combinations of homo-and heterodimers in the GeBP/ GPL family means they potentially have a high combinatorial flexibility to regulate target genes, which are so far unidentified. Indeed, in plants, heterodimeric protein interactions mediated by the Leu-zipper motif increase the repertoire of potential DNA-protein interactions (Weltmeier et al, 2006). This work allows the classification of GeBP/GPL as Leu-zipper proteins.…”
Section: Gebp/glp Proteins Are Noncanonical Leu-zipper Tfsmentioning
confidence: 94%
“…We have shown in previous work and in this study that bZIP53 heterodimerization with bZIP10 or bZIP25 increases its transactivation properties Weltmeier et al, 2006). To determine if the heterodimerization was also affecting the binding capabilities of these proteins, we incubated increasing amounts of T7-bZIP53 in the wild-type oligo-coated wells in the presence or absence of fixed amounts of bZIP10.…”
Section: Activation Of the 2s2 Seed Storage Protein Gene By Bzip53 Anmentioning
confidence: 99%
“…We have previously shown that Arabidopsis S1 bZIP proteins support strong heterodimerization with members of the group C bZIPs using two-hybrid systems in yeast and protoplasts and bimolecular fluorescence complementation (BiFC) techniques Weltmeier et al, 2006). Since two group C members, bZIP10 and bZIP25, are known activators of SSP genes (Lara et al, 2003), we surveyed the expression patterns of S1 members during seed development to identify possible partners for C-S1 interactions in this process.…”
Section: Bzip53 Is Expressed In Seed Tissues During Maturationmentioning
confidence: 99%